MEANS OF COMPOSITIONAL EXPRESSION IN THE JEWELRY DESIGN - Полевська, Єлізавета; Остапенко, Наталія; Колосніченко, Марина; Приходько-Кононенко, Ірина (SWorldJournal, 2022)
The work is devoted to the study of the means of compositional expression during the design of jewelry. The study identified the concept of composition, the principles of its formation and integral components for the creation of aesthetically harmonized